Adult Onset Henoch-Schonlein Purpura and Intussusception: A Rare Presentation. (26th September 2016) - Krishnan, Mridula; Nahas, Joseph
Abstract : We present an unusual case of a young 26-year-old male who was diagnosed with Henoch-Schonlein Purpura (HSP). Initial presentation was primarily mild gastrointestinal symptoms, which progressed to a life threatening intussusception and subsequently resolved with prompt glucocorticoid use rather than typical surgical intervention. Of importance, the patient's initial gastrointestinal symptoms without associated skin manifestations made the diagnosis difficult. In conclusion, it is important to recognize uncommon presentations of HSP as it may lead to life threatening complications and surgical intervention may be avoided with prompt treatment.